O sentido da integraç\~ao da política pública do Brasil na América do sul - Luís Maurício Martins Borges (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The present investigation text performs a historical and contemporary analysis on the Brazilian public policy trajectory, specially focused on the regional development, aiming at characterizing the pattern of the territorial integration. The inflexion one searches relies on the regional integration transformation, traditionally promoted as a means of appropriation of mercantile sources, followed by social exclusion and radical environment transformation, vis-à-vis a more intense dynamic of technology generation, regional income, social inclusion and environmental impact boundaries. For that purpose, the bibliographic review goes through the history of the South America economic integration, from a Brazilian standpoint, which highlights the economic scale and the public intervention. As from the regional integration background, one considers some market characteristics of the continent productive factors. The analysis of the Brazilian and South American investments pursuant the Plan Plus Brazil (PMB 2012-2015) and the Agenda of Priority Integration Projects 2012 (API, 2011) shows the projects connection, although with traces of the Brazilian historic pattern of production factors integration (land, work and capital), with regard of the lack of guarantee of social inclusion and environmental protection. The meaning one searches relates to the importance of the regional integration economic process, which tangle with the construction of urban, logistic and productive infrastructure, as well as with a broad and articulated Brazilian public policy, jointly with the continent's country.
Keywords: O20; 330; integration; factors of production; public policy; Brazil; South America